조리전공 남자대학생의 아침식사 빈도에 따른 식생활과 외식형태 - 김숙희(Sook Hee Kim); 정경희(Kyung Hee Joung); 채병숙(Byoung Sook Chae) (Korean journal of community nutrition, 2007)
This study was to investigate dietary life and eating-out style related to breakfast frequency of male students in culinary college. This survey was conducted using questionnaires for 110 male students at college in Hongseung. Mean height and body weight of those we investigated was 174 cm and 70.5 kg. The one to two times per week breakfast eating group was 34.55%, which is exceedingly numerous; none per week breakfast eating group was 30%; three to tow times per week breakfast eating group was 15.45%; everyday breakfast eating group was only 9.09%. The breakfast frequency was very low, and the not-eating breakfast problem is serious to think of in male college students. Mean weight, body fat and body mass index(BMI) of the everyday breakfast eating group was lower than the other group even it was not significant. The self-boarding house or dormitory living condition group was not eating breakfast was significant. So a correct dietary lift and eating habit should be taught further for male college students. The smoking group was a significant low frequency of breakfast eating, as well as the lower frequency of breakfast, or worse recognition of self health condition. Higher frequency of breakfast showed more contentment of self body weight. Cooked rice was significantly the most preferable for breakfast. The lower breakfast frequency tended to eat breads or cereals. The lower frequency of breakfast, self recognition of eating rate as speedier was significant, and tended to have a higher frequency of eating-out because of being annoyed by cooking. The lower breakfast frequency ate out more. Twenty five percent of the everyday breakfast eating group ate out because of a special day, and thirty five percent of the not eating breakfast group did so because of being annoyed by cooking. Their mean dietary evaluation grade was under the normal grade, which means that culinary college male students' dietary lives were poor. The lower frequency of breakfast and lower grade of food life evaluation, indicates the importance of nutritional breakfasts education should be improved for male culinary college students also.